Edukasi dan Pemberdayaan Masyarakat Kampung Pancasila Tlogosari Kulon melalui Pilah Sampah Eco-Enzim Biopori dan Komposter - Handajani, Mudjiastuti; Istianah, Istianah; Budiningrum, Diah Setyati; Purwanti, Hani (Jurnal Pengabdian KOLABORATIF, 2026)
Population growth has led to a significant increase in solid waste generation. In Semarang City, approximately 1,110 tons of waste are produced daily. One of the waste management initiatives implemented by the Environmental Agency is the waste bank program. However, this program has not yet been implemented in all areas. In Tlogosari Kulon Subdistrict, for example, no active waste bank group currently operates the program, despite the area being a densely populated residential zone and a flood-prone area. This condition contributes to environmental pollution, unpleasant odors, and potential disease transmission. Through this community service program, it is expected that residents of Kampung Pancasila Tlogosari Kulon will not only gain knowledge but also develop practical skills to manage household waste independently. The methods applied include interactive educational approaches and hands-on practice. The results indicate a significant increase in participants’ average level of understanding, from 42% at the initial stage to 86% after the program. This improvement was driven by direct practical activities, including waste segregation, eco-enzyme production, biopore infiltration holes, and composting. Overall, the program successfully enhanced participants’ environmental awareness, enthusiasm, and active involvement in sustainable household waste management.